Comparison of Effectiveness of Different Irrigant Agitation Techniques on Smear Layer Removal: A SEM Study - Dr. Gourav Thapak; Dr. Meera Nair; Dr. Ashtha Arya; Dr. Jahanvi Jaitly; Dr. Akanksha Sharma (The Bioscan, 2025)
Introduction: The smear layer formed during root canal instrumentation hinders the penetration of intracanal medicaments and root canal sealers into the dentinal tubules. Using irrigants like sodium hypochlorite, citric acid, EDTA, and chlorhexidine effectively removes microorganisms and the smear layer from the root canal space. Various manual and machine agitation techniques can be used to improve the distribution and flow of irrigation solutions. Materials and Methods: Conventional access opening was performed in premolars with a single canal followed by root canal instrumentation to the working length using ProTaper Universal rotary files (Dentsply), stopping when the ProTaper F3 file reached the desired length. A uniform irrigation protocol was followed in all samples. The samples were then divided into four groups: Control group (no activation), Group 1 (Manual agitation), Group 2 (EndoActivator), and Group 3 (Self-adjusting file). Then the samples were examined for smear layer removal. Results: Conventional irrigation resulted in a greater number of samples exhibiting a smear layer score of 4 in the control group. In the middle third of the root canal, the endoactivator group and the self-adjusting file demonstrated superior results. The average smear layer score was notably higher in the control and manual agitation groups in the coronal third of the canal. Conclusion: The use of self-adjusting files may serve as a complementary method to root canal irrigation for the removal of the smear layer. However, none of the irrigation activation techniques we examined were able to completely eliminate the smear layer.